2021
DOI: 10.3390/w13223282
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Impact of Land-Use Change on Runoff Variation Trend in Luojiang River Basin, China

Abstract: To reveal the influence process of land use changes on runoff variation trends, this paper takes the Luojiang River of China as the study area, and the Soil and Water Assessment Tool (SWAT) model was constructed to quantitatively analyze the impact of different land uses on runoff formation in the watershed, and used the Cellular Automata-Markov (CA-Markov) model to predict future land use scenarios and runoff change trends. The results show that: (1) the SWAT model can simulate the runoff in the Luojiang Rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…(2) Difference between LU and PREP on AWRs change Most studies have shown that surface vegetation can reduce water resources in basins, but the degree of reduction has not been quantified [54,55]. Through the VAR model constructed in this study, it was found that the contribution rates of AD, WD, GD, CD, and PREP to changes in AWRs were 23.76%, 4.40%, 4.34%, 4.56%, and 6.09%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Difference between LU and PREP on AWRs change Most studies have shown that surface vegetation can reduce water resources in basins, but the degree of reduction has not been quantified [54,55]. Through the VAR model constructed in this study, it was found that the contribution rates of AD, WD, GD, CD, and PREP to changes in AWRs were 23.76%, 4.40%, 4.34%, 4.56%, and 6.09%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They found that built-up area LU has a significant matter in the runoff, but there is no discernible difference in the amount of water flowing out of the streams caught by bamboo and pine plantations, as well as those detected by cultivated land and tea plantations. Also, He et al (2021) studied the impacts of the development of LU on runoff at the Luojiang River in China. This study suspects that runoff will increase by 2050 due to LU change.…”
Section: Impact Of Lu On Runoffmentioning
confidence: 99%
“…The annual average rainfall is 1890 mm, but the distribution of rainfall in space and time is extremely uneven. The rainfall in the middle of a year is mainly concentrated in May to September, accounting for 75% of the total rainfall of the year [41,42].…”
Section: Study Areamentioning
confidence: 99%